Industrial Relations between Ojek Online Drivers with PT. Gojek Indonesia Branch Of Surakarta - Chadijah, Devi Intan; Wijaya, Mahendra; Soemanto, Raden Bagus (Universitas Muhammadiyah Yogyakarta, 2019)
This study to analyze about understanding the driver and the company of Gojek about Partnership Agreements which is different with Work Agreements that has been set up by labor law in Indonesia, so it became a new study, and then analyze to know the relation that partnerships between the driver, company, government and consumer. This research is assessed using the theory social exchange Peter Blau. The method of this study is naturalistic inquiry. We find there is a different understanding between the driver with the company of Partnership Agreements. According to the drivers, contract offered by the company Gojek have not answered the rights of driver as a partner or as worker, like social security, a system of compensation, and working time. Partnership Agreements that should have mutually beneficial, but in fact a working relationship which is interwoven as a working relationship on workers that have must always be subject to any company policy. Therefore the drivers agree if online transportation of ojek arranged by the government. The absence of a labor union official and there is no industrial relations commonly called Tripartite between the driver, company, government and consumer.